Legal Strength of Consumer Financing Principal Agreements Post The Decision of the Constitutional Court No. 18/puu-xvii/2019 - Nasrullah, Nasrullah (Universitas Negeri Gorontalo, 2021)
AbstractAfter the Constitutional Court Decision No. 18/PUU-XVII/2019, fiduciary certificates no longer have direct executive power and the determination of promise injuries is not determined unilaterally by financing creditors but based on agreements between creditors and debtors. This certainly has an impact on fulfilling the rights of business actors (creditors) and ignoring binding powers on the principal financing agreement and fiduciary certificate. The purpose of this study is to find out whether the Constitutional Court Decision No. 18 / PUU-XVII / 2019 is contrary to the main agreement of consumer financing, and How the legal strength of the consumer financing agreement after The Constitutional Court Decision No. 18 / PUU-XVII / 2019. The type of research used is a type of normative research with a focus on the statutory approach and the conceptual approach. The results of the study explained that the principal agreement of consumer financing with The Decree no. 18 / PUU-XVII / 2019 there is a conflict (conflict) but only a pseudo conflict (not a textual conflict) because in terms of intent and purpose there is no conflict, but potentially less balance the legal interests of business actors. Constitutional Court Decision No. 18/PUU-XVII/2019 has destabilized the existence of the deed of the principal financing agreement. The minimum limit of proof of the principal financing agreement is not perfect and no longer binding as the law for both parties and the deterioration of the evidentiary value of the deed of the principal agreement and the legal strength of the fiduciary certificate and the principal financing agreement is in the determination of the court. There need to be regulations that regulate sanctions if consumers deliberately delay their obligations to pay credit installments and the need for the participation of community institutions, business actors, and including the government to socialize.